2002
DOI: 10.1021/bi026590q
|View full text |Cite
|
Sign up to set email alerts
|

Iron−Sulfur Clusters of Biotin Synthase In Vivo:  A Mössbauer Study

Abstract: Biotin synthase, the enzyme that catalyzes the last step of the biosynthesis of biotin, contains only [2Fe-2S](2+) clusters when isolated under aerobic conditions. Previous results showed that reconstitution with an excess of FeCl(3) and Na(2)S under reducing and anaerobic conditions leads to either [4Fe-4S](2+), [4Fe-4S](+), or a mixture of [4Fe-4S](2+) and [2Fe-2S](2+) clusters. To determine whether any of these possibilities or other different cluster configuration could correspond to the physiological in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
34
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 27 publications
7
34
0
Order By: Relevance
“…Furthermore, all AdoMet radical proteins require S-adenosylmethionine as a cofactor to initiate radical-based catalysis. The iron-sulfur clusters of several members of the family have been characterized by electron paramagnetic resonance (EPR), resonance Raman, and Möss-bauer spectroscopy (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). For pyruvate formate-lyase-activating enzyme (PFL-AE) and biotin synthase (BioB), it was shown using Mössbauer spectroscopy that the [4Fe-4S] cluster contains one iron atom, which is not ligated by a cysteine residue, and that AdoMet binds to this special iron site of the cluster (17,18).…”
mentioning
confidence: 99%
“…Furthermore, all AdoMet radical proteins require S-adenosylmethionine as a cofactor to initiate radical-based catalysis. The iron-sulfur clusters of several members of the family have been characterized by electron paramagnetic resonance (EPR), resonance Raman, and Möss-bauer spectroscopy (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). For pyruvate formate-lyase-activating enzyme (PFL-AE) and biotin synthase (BioB), it was shown using Mössbauer spectroscopy that the [4Fe-4S] cluster contains one iron atom, which is not ligated by a cysteine residue, and that AdoMet binds to this special iron site of the cluster (17,18).…”
mentioning
confidence: 99%
“…57 FeCl 3 solution was prepared using a modified literature procedure [35]. 0.0146 g 57 Fe (99.8% purity) was dissolved in 1 mL 37% HCl (over 2 d) and the solution was exposed in air and light until the color turned to brown-yellow.…”
Section: Methodsmentioning
confidence: 99%
“…and used for cloning and expression [35]. Overexpression and purification of nFbpA (Neisseria Gonorrhoeae) was performed by a literature method [37].…”
Section: Cloning and Protein Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the [4Fe-4S] 2+ cluster is rapidly oxidized in the absence of the [2Fe-2S] 2+ cluster and bound substrates [17], most likely resulting in the formation of an inactive apoenzyme following turnover in aerobic bacteria. Mössbauer spectra of whole cell preparations of E. coli expressing recombinant BioB indicate that <35% of the enzyme contains a [4Fe-4S] 2+ cluster, probably due to the air-sensitivity of this cluster [18,19]. Since the biotin requirements of bacteria are very low, on the order of 100-1000 molecules per cell [20], it has been suggested that BioB may be a stoichiometric reactant that is degraded after a single turnover.…”
Section: Introductionmentioning
confidence: 99%